Karakteristik Minyak Ikan Nila (Oreochromis niloticus) Hasil Pemurnian Menggunakan Arang Aktif dan Bentonit pada Hasil Samping Limbah Fillet Ikan Nila PT. Aquafarm Nusantara Semarang - Sumartini; Supriyanto; Pudji Hastuti (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
PT Aquafarm Nusantara is known as a modern industry in fish processing produced Tilapia Fillet as the main product that is routinely exported to several countries. Therefore, there are still some by products left such as bones, scales, skin, the content of belly, and head. This study conducted aimed to seek the characteristics and the quality of fish oil after purification. The method used was an experimental laboratory using eight different treatments on pale dose (charcoal) 1%, 2%, 3%, bentonite 1%, 2%, 3%, active charcoal 2% : 1%, and bentonite:active charcoal 1%, 2%. Parameters used are moisture content, melting point, free fatty acid, peroxide and iodin value, brightness and clarity. The best result of parameter analysis was showed by combining betonit: actice charcoal (2%:1%), it showed the moisture content 0.05 ± 0,02%, iodin number 121,87±2,55, peroxide number 7,92±0,00%, FFA 0,23±0,05, brightness 55,67±0,09% (L*),-1,09±0,03 (a*), 23,36 ±0.03(b*), and clarity 82,79 ± 0.51%T.